Isolation and Identification of a Potential Amylolytic Probiotic Bacterium from the Gut of Jundiá Catfish, Rhamdia quelen. - Poletto,Tatiana Vieira (2018)
ABSTRACT This study aimed to isolate a potential probiotic amylolytic strain from the gut of jundiá catfish to improve carbohydrate digestibility in fish. Two of 31 strains isolated from the foregut of Rhamdia quelen were able to grow on starch-agar medium and were considered amylolytic. The strain that presented higher amylolytic potential, based on a qualitative amylase assay, was chosen. The strain was phenotypically characterized and analysed to determine bile and pH tolerance and extracellular quantitative amylase activity. The probiotic candidate, identified as Aeromonas veronii, showed the ability to survive stresses from a range of pH and bile salt conditions and secreted an interesting enzymatic profile, which may exhibit a synergistic effect when combined with the enzymes secreted by the jundiá catfish, improving carbohydrate digestion in the host. The results demonstrated the potential of A. veronii to improve the digestion process in jundiá by providing exogenous enzymes for the breakdown and absorption of nutrients.